Fatty acid based phase change materials for thermal storage applications / Hadi - Hadi, - (2016)

(untitled)
A novel phase change material (PCM) made from fatty acids is proposed for usage in domestic water heating applications in tropical countries. The PCM is made from a binary mixture of myristic acid (MA) and palmitic acid (PA), having a range of phase transition temperature between 40 to 45 °C. Acid based surfactant such as sodium stearate (SS), sodium laurate (SL), sodium myristate (SM), and sodium palmitate (SP) was also proposed as additives to improve the latent heat capacity and depress the phase transition temperature of the MA/PA mixture. The thermal properties and thermal conductivity of both MA/PA and MA/PA+ surfactants were measured using differential scanning calorimetry (DSC) thermal analysis and KD2Pro thermal conductivity analysis. The results have shown that the addition of 5 wt.% SS, 10 wt.% SL, 5 wt.% SM, and 5 wt.% SP to MA/PA binary mixture was effective in depressing the phase transition temperature and reducing the undercooling problem, while increasing the latent heat capacity and thermal conductivity of the eutectic PCM. Cyclic thermal tests have also shown good retainments of thermo-physical properties in the MA/PA+surfactants samples, with only a small change in phase transition temperature and latent heat capacity, and have good chemical structure stability and small volume changes, even after long periods of thermal cyclic tests. To further improve the thermal conductivity of the MA/PA and MA/PA+surfactants, a porous material addition into the mixture was subsequently proposed. The proposed material, in the form of shorea javanica derived from purified damar gum trees, was impregnated into the mixtures to form a eutectic composite phase change materials (CPCMs). The thermal properties, thermal conductivity, and thermal stability of CPCM were measured using Differential Scanning Calorimetry (DSC) thermal analysis, hot disc thermal conductivity analyzer, and Simultaneous Thermal Analyzer (STA), respectively. In addition, a Fourier Transform Infra-Red (FT-IR) spectrophotometer was used to evaluate the occurrence of iv a chemical reaction between the fatty acid binary mixture and shorea javanica in the CPCM. The results shown that the addition of 2 to 3 wt.% of shorea javanica into the fatty acid eutectic mixture has improved the thermal conductivity of the CPCM without major changes on its thermo-physical properties and occurrence of chemical reactions. The prepared CPCMs have also shown good thermal performance and thermal stability. Finally, the compatibility of the CPCMs to container materials of stainless steel and carbon steel was evaluated using gravimetric analysis. The results shown that both metals have good corrosion resistance against the prepared eutectic CPCMs for an extended period of use. Thus, this comprehensive study has successfully developed a novel thermal energy storage materials based on fatty acids which meet the standards of thermal properties, physical, and chemical properties requirement for thermal energy storage application in particular to domestic solar water heating system.